Retoryka literacka versus semantyka terroru. Instytucje zrzeszające niemieckich literatów w latach 1933–1945 - Wolting, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
This contribution undertakes the question of the condition of German writers during the Nazi rule. It describes the associations of German writers, both in Germany and in emigration. The subject will be investigated in the context of the emergence of the new political, symbolic and cultural fields. The main research question is the search by the German intellectuals for their social place in the changing reality of the 1933–1945 period. According to the author, Germany’s cultural elite in 1933 started the emigrant existence beyond institutions, founded upon literary, journalistic and artistic work which was individually conducted.
Keywords: niemieccy pisarze; rządy nazistowskie; emigracja